(untitled) (Italian Review of Legal History, 2019)
The juvenile question has been traced by historiography above all through the prism of repression and prevention; in twentieth-century Italy the need for social control, "dominant thought", has complicated the construction of the right for minors and minors. In fact, civil codification, "adult-friendly", assigned the rights to the rational and autonomous subject, as if to re-propose the liberal paternalism of Stuart Mill, about minors to be protected in the first place by themselves. The system envisaged minors above all to impose the ancient on it honors the father; even if the civil code of 1942 did not foresee a total subjection of the children with respect to parental authority, before fascism and still in the fifties the parental authority was understood as ’remedy’ to the inability to act of the child, obstacle to the action of the State in the order and disorder of the family. At the beginning of the century the "legal protection of minors" seemed "unknown to our law and outside the law", inadequate especially in the pitiless comparison with European and overseas legislation; the comparison with a ‘happy elsewhere’ - first and foremost the Children Act of 1908 - would have been a constant in national policies for children and adolescents, from the Circular of the Minister of Justice V.E. Orlando to the Code Project for minors. Far from ‘specialism’ - a figure of the italian scientia iuris - the juvenile law had an ‘interdisciplinary’ figure, based above all on the link between law and pedagogy; in 1910 Orlando was speaking at the Milan Forensic Pedagogical Institute of the "always and forever" pre-eminent right for minors, that of "educational protection", "education, albeit forced". In liberal Italy the planning was significant and the debate was significant; the Ferri Project was a ’final act’, intended to distinguish between children and adolescents and to build a special criminal justice system with respect to that for adults. In the years of fascism - even in this matter anything but parenthesis - legislation was tightened, with the institution of the Maternity and Childhood National Opera - active until 1975 - the Balilla National Opera, the Juvenile Court (Rd . 1404/1934). The regime intended to mark the passage of the juvenile issue from the criminal to the "social" field; "re-education" was central, as reiterated in 1941 by the Minister of Justice Dino Grandi. Rd. 140/1934 was linked to the penal and penal-procedural codification (1930) and was a "forerunner" of civil codification (1942). In the doctrine of the 1950s the "autonomy" of juvenile law was born with the juvenile court; sporadic notes were reserved for the Constitution and the Geneva Declaration of Universal Children’s Rights (1924). Despite a merely exhortatory horizon, the international sources later allegedly "urged" the Italian legislator, above all on the problematic level of implementation of the principles. The juvenile law developed as a sort of judge made law - built above all by the presidents of the juvenile court, Radaelli, Baviera, Cividali, Meucci, Moro, Vercellone, Occhiogrosso, Fadiga - problematic profile for the prevailing legalistic Italian legal culture, hostile to the wide discretion, exercised by the judge specialized in jurisdictional and administrative matters. In 1951 the Italian Union of judges for minors was also born, then the Association, the engine of the legislative process; in 1971 the organic plan of the "specialized judge" was established. The juvenile law was complicated by the changes of custom, which invested the society: in the early twentieth century the debate between jurists, judges, politicians, social scientists was inscribed in the horizon of the paternal and / or state authority, not in that of freedom and autonomy of the minor. With a change of perspective, at the Constituent Assembly Aldo Moro discussed a "problematic" right, given the subject’s inability to act, but "authentic". As if to anticipate the best interest of the child, law 431/67 - called special adoption - gave the Court the task of "promoting and defending the rights of the child". Elia - who was the speaker of a dense sentence of the Consulta in 1981 - argued that the "center of gravity" of the system shifted "from the interest of the adopter to the one adopted". But there were problems: in front of the very real dramas about the destination of the child - single and problematic mother or Institute - Jemolo asked himself "where is the minor’s interest", a question in his opinion not dissolved by the law, which he had entrusted to the judge a task that is not his. Even the world of law was surrounded by new sensitivities and social transformations: in the mid-seventies the theme of the "method" was posed, with the transformation of the "juvenile right", from "the right of minors to the rights of minors’ rights". With the family law reform of 1975, the "old" child law seemed destined to give way to a "new" one; for Alfredo Carlo Moro set the "unified" subject, and "Pierino, Maria" entered the scene; in the light of the 1989 International Convention on the Rights of the Child, ratified in Italy two years later, Moro affirmed that the discourse on "rights" had to rest on "implementation". On the other hand it was observed that the legislator could not establish by law the contents of the rights - first of all that to education - if not with general and abstract criteria, and that the minor was not considered by law as a subject of right, but as a recipient of decisions made by others, parents, guardians, judges. In 1970 Cividali staged a "new judge", committed to promoting the rights of the child, empathetic with the "person", rather than intent on applying the law "coldly". The polarity between the respect of the rules, for the protection of all children, and the decision in the best interest of that particular child, even in contravention of the law, burst with the ’famous case’ of Serena Cruz, removed by the Turin Juvenile Court to the family, who had adopted it illegally; that "celebrated case" staged the gap between legality and "true justice". As for the relationship between minors and institutions, meant for re-education, the practice shows that, from fascism to the republic, political discontinuity is matched by institutional continuity, even in the violence exercised on minors; hence the "provocation", the creation of a "Tribunal for the defense of minors". Not even the 1988 Code of Juvenile Criminal Procedure, intended to "educate by empowering", seemed to ensure an effective "guarantee" for minors.